Effects of a 5-minute classroom-based physical activity on on-task behavior and physical activity levels (Kinesiology, 2018)
Objectives: Explore the effectiveness of a five-minute classroom-based physical activity (5min-Class-PA) to keep student behavior on task while increasing physical activity and energy expenditure during school days.Design: Randomized control trial. Multiple baselines across subjects design was implemented to assess on-task behavior during academic lessons (e.g. Mathematics, Science, Language, Art). Observers were blinded to study condition. A quasi-experimental design was implemented to assess PA volume and energy expenditure using SenseWear Armband body monitor (BodyMedia Inc., Pittsburgh, PA, USA).Setting: Elementary school, grades 1-4Participants: A convenience sample of elementary school pupils (6-10yrs). A total of eight class departments or two class departments per grade (first–fourth) were included by random selection. All pupils from selected class departments were asked to participate (total 149) and 126 (85%) had no health aberrations and returned parent signed informed agreement on participation.Intervention: Five-minute PA daily in the middle of a 45-min academic lesson by imitating video animations projected on the school board for 12 weeks.Outcome measures: Primary: on-task behavior during academic lessons. Secondary: physical activity volume and energy expenditure during school day.Results: When 5min-Class-PA was implemented, initially high on-task behavior during the first part of the lesson (91.42% and 94.8% for 6-8 and 8-10-year-old pupils, respectively) was not significantly changed after the 5min-Class-PA. In contrast, when 5min-Class-PA was not implemented, on-task behavior during the second part of the lesson decreased (by 3% and 4% for 6-8- and 8-10-year-old pupils, respectively). Additionally, after the 5min-Class-PA was systematically introduced, on-task behavior systematically improved. The results also indicate there is a significant increase or improvement in PA levels and energy expenditure during school days.Conclusion: On-task behavior during academic lessons and daily in-school PA levels can be improved by implementing a 5min-Class-PA.